PENGARUH MATA PELAJARAN PPKn TERHADAP PENGETAHUAN MORAL SISWA DI SMA NEGERI 1 PASIR PENYU KABUPATEN INDRAGIRI HULU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is driven by the rapid development of the times, resulting in many students being immoral, and PPKn subjects are used as a means to make students better. The question of this study is whether civic education has an impact on the moral knowledge of SMA Negeri 1 Pasir Penyu students. The purpose of this study was to determine whether civic education had an impact on the moral knowledge of SMA Negeri 1 Pasir Penyu students. This research method uses quantitative methods, using statistical analysis techniques with descriptive methods. The data collection tool used a questionnaire or questionnaire consisting of 34 statements. The population of this study consisted of SMA Negeri 1 Pasir Penyu students only, with a total of 818 students in grades X, XI, XII, using random sampling techniques, a 10% sample of the total population was 82 respondents. The findings suggest that there is a positive effect between the two Civics subjects on the moral knowledge of students at SMA Negeri 1 Pasir Penyu. This can be proven by simple linear regression analysis using the SPSS application, namel y = 33.098 + 0.741X. The result of the above formula can be interpreted as a constant 33.098, that is, the consistency value of the moral knowledge variable is 33.098, and the regression coefficient of X is 0.741, that is to say the addition of 1% value in Civics subjects will increase moral knowledge by 0.789. The positive coefficient means that the Civics subject (X) has a positive effect on Moral Knowledge (Y). Key Words: Influence, Civics subject, Moral knowledge